Protection of intestinal injury during heat stroke in mice by interleukin‐6 pretreatment. (2nd January 2015) - Phillips, Neil A.; Welc, Steven S.; Wallet, Shannon M.; King, Michelle A.; Clanton, Thomas L.
Abstract : Key points: Heat stroke afflicts thousands of humans each year, worldwide. The immune system responds to hyperthermia exposure resulting in heat stroke by producing an array of immunological proteins, such as interleukin‐6 (IL‐6). However, the physiological functions of IL‐6 and other cytokines in hyperthermia are poorly understood. We hypothesized that IL‐6 plays a protective role in conditions of heat stroke. To test this, we gave small IL‐6 supplements to mice prior to exposing them to hot environments sufficient to induce conditions of heat stroke. Pretreatment with IL‐6 resulted in improved ability to withstand heat exposure in anaesthetized mice, it protected the intestine from injury, reducing the permeability of the intestinal barrier, and it attenuated the release of other cytokines involved in inflammation. The results support the hypothesis that IL‐6 is a 'physiological stress hormone' that plays an important role in survival during acute life‐threatening conditions such as heat stroke. Abstract: The role of interleukin‐6 (IL‐6) in hyperthermia and heat stroke is poorly understood. Plasma IL‐6 is elevated following hyperthermia in animals and humans, and IL‐6 knockout mice are more intolerant of severe hyperthermia. We evaluated the effect of IL‐6 supplementation on organ injury following severe hyperthermia exposure in anaesthetized mice. Two hours prior to hyperthermia, mice were treated with 0.6 μg intraperitoneal IL‐6, or identical volumes of saline in controls. Mice were anaesthetized, gavaged with FITC–dextran for measures of gastrointestinal permeability, and exposed to incremental (0.5°C every 30 min) increases in temperature. Heating stopped when maximum core temperature ( T c ) of 42.4°C was attained ( T c, max ). The mice recovered at room temperature (≈22°C) for 30 or 120 min, at which time plasma and tissues were collected. IL‐6‐treated mice, on average, required ≈25 min longer to attain T c, max . Injury and swelling of the villi in the duodenum was present in untreated mice after 30 min of recovery. These changes were blocked by IL‐6 treatment. IL‐6 also reduced gastrointestinal permeability, assayed by the accumulation of FITC–dextran in plasma. Plasma cytokines were also attenuated in IL‐6‐treated animals, including significant reductions in TNFα, MCP‐1 (CXCL2), RANTES (CCL5) and KC (CCL5). The results demonstrate that IL‐6 has a protective influence on the pattern of physiological responses to severe hyperthermia, suggesting that early endogenous expression of IL‐6 may provide a protection from the development of organ damage and inflammation.